Ética y Recursos Humanos (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
This article provides an overview of the fascinating and complex area of business ethics, people and Human Resources. The authors re-examine several fundamental aspects of these three key concepts with a view to highlighting those essential elements of Human Resources, people and business ethics which are often overlooked under the pressure of day-to-day demands. Moreover, this article seeks to present some of the challenges and concerns currently affecting Human Resources.
Keywords: Human Resources; people and Bussiness Ethics